2010
DOI: 10.1097/qad.0b013e328340fe76
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system disorders after starting antiretroviral therapy in South Africa

Abstract: Objective To describe the spectrum of central nervous system (CNS) disease during the first year of antiretroviral therapy (ART), and to determine the contribution of neurological immune reconstitution inflammatory syndrome (IRIS). Design A prospective observational cohort study conducted over a 12-month period at a public sector referral hospital in South Africa. Methods HIV seropositive patients who developed new or recurrent neurological or psychiatric symptom(s) or sign(s) within the first year of star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 20 publications
0
40
0
3
Order By: Relevance
“…According to one study, as many as 21% of patients in South Africa have developed Mycobacterium-related CNS-IRIS. 60 Given that one-third of the world's population has been infected with tuberculosis, a greater evidence of mycobacterial CNS-IRIS may emerge as ART increases in availability worldwide. If a patient presents with clinical deterioration and meningeal enhancement on MRI or communicating hydrocephalus in the context of ART initiation with adequate treatment for mycobacteria, IRIS should be strongly considered in the differential diagnosis.…”
Section: Bacterial Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…According to one study, as many as 21% of patients in South Africa have developed Mycobacterium-related CNS-IRIS. 60 Given that one-third of the world's population has been infected with tuberculosis, a greater evidence of mycobacterial CNS-IRIS may emerge as ART increases in availability worldwide. If a patient presents with clinical deterioration and meningeal enhancement on MRI or communicating hydrocephalus in the context of ART initiation with adequate treatment for mycobacteria, IRIS should be strongly considered in the differential diagnosis.…”
Section: Bacterial Pathogensmentioning
confidence: 99%
“…60 Cryptococcal infections may be associated with 10% to 30% of all CNS-IRIS, 53 most often clinically manifest as aseptic recurrence of prior meningitis and rarely as intracranial cryptococcoma.…”
Section: Fungal Pathogensmentioning
confidence: 99%
“…In one study, paradoxical neurologic worsening was observed in 28% of South African patients started on HAART. 4 IRIS has also been described with opportunistic parasitic diseases unique to the developing world, such as schistosomiasis, strongyloidiasis, and leishmaniasis.…”
mentioning
confidence: 99%
“…Of these patients, four had meningitis; five had intracranial space occupying lesions, mainly multiple and with perilesional edema; five had both meningitis and space occupying lesions; one had radiculomyelitis; and one had spondylitis [8]. A recent prospective observational cohort study by Asselman et al [10] in South Africa found CNS tuberculosis in 36% of CNS diseases diagnosed during the first year of HAART; paradoxical neurological IRIS comprised 21% of the diagnoses. In 2012, Guevara-Silva et al reported their experience at a Mexican neurological center, where they found that 9.3% of patients developed cerebral IRIS, two of whom had tuberculosis, and those patients showed a good prognosis [11].…”
Section: Discussionmentioning
confidence: 99%